PENGGUNAAN HADIS-HADIS PADA SKRIPSI MAHASISWA IAIN PONTIANAK - Wajidi Sayadi (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2019)
This research was conducted to find out how the writing and quality of the Hadith of the Prophet Muhammad in the thesis of students of the Department of Islamic Education, Tarbiyah Faculty and Teacher Training of IAIN Pontianak, in academic year 2013/2014. The research methods used includes; First, do takhrij al-hadith; Second, do I’tibar al-hadith; Third, examine the narrators' personalities and methods of transmission by using, among others, the knowledge of al-jarh wa at-ta'dil. Fourth, conclude the results of the study. There are 100 theses studied, only 25 theses (25%) have hadiths in them, and 75 theses (75%) that do not include hadiths. There are two types of hadith writing in student thesis: First, hadith are written in Arabic text and their translations. Second, only the translation of the hadith was written. In writing the hadith of the Arabic text there are several errors. There is even a hadith text that is different from the translation. This happens, because most of the thesis is about improving the reading of the Qur'an in a particular school. The quality of the hadiths in student theses is 66 Sahih hadiths, 7 Hasan hadiths, 8 Daif Hadiths, 2 very daithic hadiths, 1 false hadith, 1 mauquf hadith, and 1 not known quality of hadith. Students' understanding of the hadith writing and the quality of the hadith is still lacking. Thesis supervisors and examiners are negligent in seeing the traditions of the hadith used by students. [Penelitian ini dilakukan untuk mengetahui bagaimana penulisan dan kualitas hadis-hadis Nabi Muhammad SAW dalam skripsi mahasiswa Jurusan Pendidikan Agama Islam Fakultas Tarbiyah dan Ilmu Keguruan IAIN Pontianak tahun akademik 2013/2014. Adapun metode penelitian yang digunakan antara lain; Pertama, melakukan takhrij al-hadits; Kedua, melakukan I’tibar al-hadits; Ketiga, meneliti pribadi para periwayat dan metode periwayatannya dengan menggunakan antara lain ilmu al-jarh wa at-ta’dil. Keempat, menyimpulkan hasil penelitian. Ada 100 skripsi yang diteliti, hanya 25 skripsi (25 %) yang ada hadis di dalamnya, dan 75 skripsi (75 %) yang tidak mencantumkan hadis. Ada dua macam cara penulisan hadis dalam skripsi mahasiswa: Pertama, hadis ditulis dalam teks Arab dan terjemahannya. Kedua, hanya terjemahan hadisnya yang ditulis. Dalam penulisan hadis teks Arabnya terdapat beberapa kekeliruan. Bahkan ada yang teks hadisnya berbeda dengan terjemahannya. Hal ini terjadi, karena kebanyakan skripsi mengenai upaya peningkatan membaca al-Qur’an di suatu sekolah tertentu. Adapun kualitas hadis-hadis dalam skripsi mahasiswa, adalah 66 hadis Sahih, 7 hadis Hasan, 8 hadis Daif, 2 hadis sangat daif, 1 hadis palsu, 1 hadis mauquf, dan 1 hadis yang belum diketahui kualitasnya. Pemahaman mahasiswa dalam hal penulisan hadis dan kualitas hadis masih sangat kurang. Para pembimbing dan penguji skripsi lalai dalam melihat keshahihan hadis yang digunakan oleh mahasiswa]. Kata Kunci: Hadis, Skripsi, Mahasiswa, Sahih, Da’if, dan Palsu.